Intelligent decision technologies 2019 : proceedings of the 11th KES International Conference on Intelligent Decision Technologies (KES-IDT 2019).: proceedings of the 11th KES International Conference on Intelligent Decision Technologies (KES-IDT 2019). Volume 2 ([2019]) - Unknown
No abstract available